Distal Tibial Bone Grafting for Talar Dome Osteochondral Lesions: Novel Technique and Clinical Results. Issue 1 (19th August 2016) - Haskell, Andrew; Kim, Todd S.
Category: Arthroscopy Introduction/Purpose: Osteochondral lesions (OCLs) of the talar dome are very common and often cause disabling pain. Smaller lesions are treated successfully with bone marrow stimulation techniques such as arthroscopic microfracture. Controversy exists, however, about the optimal treatment for larger, cystic lesions. Osteochondral grafting, either allograft or autograft, is the most common technique but is not optimal, as it requires allograft tissue or donor autograft from another joint. This procedure often requires a malleolar osteotomy for access to the talus, which carries inherent morbidity. We describe a technique of treating large, cystic OCLs by transferring structurally intact autograft from the distal tibia to the talus, which can be performed without osteotomy, does not require allograft tissue, and can be obtained from a local donor site. Methods: Twenty-three ankles in 22 patients underwent distal tibial bone grafting procedure for treatment of large, cystic OCLs of the talus. A cancellous autograft bone plug was harvested from the ipsilateral distal tibial metaphysis and implanted into the drilled out talar lesion through a small anterior arthrotomy. The graft may be placed oblique to the talar surface and contoured to match the level of the surrounding subchondral bone. Allograft bone chips were used to backfill the distal tibia donor site. Pre-operative and final post-operative data was available for 11 patients with a minimum of 6 months follow-up. Validated patient reported outcomes scores and other data collected included Foot Function Index (FFI), AOFAS hindfoot score, SF-12, and Visual Analog Scale (VAS) pain. Final postoperative data also included VAS patient satisfaction and PROMIS validated and normalized lower extremity function and pain scores. Comparisons were made by paired t-Test and data reported mean±SD. Results: Mean patient age was 47 (range 15-70). Seven of 11 patients were female. Lesions were all medial and measured 122 mm2 (range 80-160) by 8 mm depth (range 6-9). Average follow-up was 23 months (range 7-33). There were no complications or reoperations. Significant improvement (p < 0.05) occurred in AOFAS Hindfoot score (67±16 to 88±12), FFI (55±20 to 22±17), VAS pain score (6.3±2.4 to 1.4±1.5), and SF-12 (31±9 to 50±10). Final VAS patient satisfaction was 8.5±1.8/10, and 10 of 11 patients reported they would have the procedure again. PROMIS scores (normalized to population mean 50±10) at final follow-up were physical function: 53±6; pain intensity: 40±10; and pain interference: 45±6. Eight of 9 patients who were employed were able to return to full duty without limitation. Conclusion: Distal tibial bone grafting is a safe and effective treatment for large talar OCLs. This technique avoids the need for allograft tissue, distant donor site morbidity, and malleolar osteotomy. Early to mid-term clinical outcomes, including validated outcomes scores, are encouraging. Our results are comparable if not better than the results reported with other described techniques for large talar OCLs. Further follow-up is necessary to define longer-term results, to assess cartilage healing with advanced imaging or second look arthroscopy, and to help define the exact role for this technique in treatment of talar osteochondral lesions.